Osteoclastic and pleomorphic giant cell tumors of the pancreas: A review of clinical, endoscopic, and pathologic features - Moore, Jill C (Baishideng Publishing Group Co., Limited, 2010)
Giant cell tumors of the pancreas come in three varieties-osteoclastic, pleomorphic, and mixed histology. These tumors have distinctive endoscopic, clinical, and cytological features. Giant cell tumors have a controversial histogenesis, with some authors favoring an epithelial origin and others favoring a mesenchymal origin. The true origin of these lesions remains unclear at this time. These are also very rare tumors but proper identification and differentiation from more common pancreatic adenocarcinoma is important. The risk factors of these tumors and the prognosis may be different from those associated with standard pancreatic adenocarcinoma. Recognition of these differences can significantly affect patient care. These lesions have a unique appearance when imaged with endoscopic ultrasound (EUS), and these lesions can be diagnosed via EUS guided Fine Needle Aspiration (FNA). This manuscript will review the endoscopic, clinical, and pathologic features of these tumors.